2017
DOI: 10.1128/jvi.00056-17
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Alternative Modified Live Influenza B Virus Vaccine

Abstract: Influenza B virus (IBV) is considered a major human pathogen, responsible for seasonal epidemics of acute respiratory illness. Two antigenically distinct IBV hemagglutinin (HA) lineages cocirculate worldwide with little cross-reactivity. Live attenuated influenza virus (LAIV) vaccines have been shown to provide better cross-protective immune responses than inactivated vaccines by eliciting local mucosal immunity and systemic B cell- and T cell-mediated memory responses. We have shown previously that incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(73 citation statements)
references
References 69 publications
9
64
0
Order By: Relevance
“…Thus, reverse genetics was used to generate the following viruses: Ty/04 att (H3N2), Ca/04 att (H1N1), B/Bris att (Victoria lineage), and B/Wisc att (Yamagata lineage). The Ty/04 att , Ca/04 att , and B/Bris att viruses have been previously described ( 23 25 ), while the B/Wis att virus was prepared for this study ( Table 1 ). Like the B/Bris att virus, the B/Wis att virus displayed a ts phenotype in vitro that is typically associated with attenuation in vivo (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, reverse genetics was used to generate the following viruses: Ty/04 att (H3N2), Ca/04 att (H1N1), B/Bris att (Victoria lineage), and B/Wisc att (Yamagata lineage). The Ty/04 att , Ca/04 att , and B/Bris att viruses have been previously described ( 23 25 ), while the B/Wis att virus was prepared for this study ( Table 1 ). Like the B/Bris att virus, the B/Wis att virus displayed a ts phenotype in vitro that is typically associated with attenuation in vivo (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…QIV-vaccinated mice also survived challenge with the B/Bris strain carrying the PB2 F406Y mutation and by 5 dpc showed no evidence of virus replication in lungs and NTs. We have previously shown that the PB2 F406Y mutation increases the virulence for mice of the wild-type B/Bris strain (it also slightly increases the virulence of B/Wisc) ( 25 ). Unexpectedly, the B/Bris challenge dose (≤10 50% lethal doses [LD 50 ]) was sufficient to cause significant body weight loss in the QIV-vaccinated/challenged mice compared to the PBS-PBS mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a prototypical influenza B virus engineered with a similar tsHA strategy resulted in a stable virus over multiple passages in tissue culture and eggs, and attenuated in vivo . In mice, a single intranasal dose of the IBV tsHA virus offered protection against lethal homologous and heterologous IBV challenges (Santos et al, 2017a ).…”
Section: Efforts To Avert the Setbacks In Vaccine Usementioning
confidence: 99%
“…Live attenuated vaccine platforms have been among the most explored over the years (reviewed in [24]). In addition to the coldadapted LAIVs developed in the 60's that form the basis of the current LAIVs approved for human use, alternative LAIV approaches have been developed that include modifications and deletions to the NS1 gene segment, generation of M2 deficient viruses, alternative virus backbones with temperature sensitive phenotypes, among others [25][26][27][28][29][30][31]. We have previously shown that genome re-arrangement is a suitable strategy for the development of influenza A virus LAIVs [32].…”
Section: Introductionmentioning
confidence: 99%